Groups with Infinitely Many Ends Acting Analytically on the Circle - Navas-Flores, A (John Wiley and Sons Ltd., 2019)
This article is inspired by two milestones in the study of non-minimal group actions on the circle: Duminy s theorem about the number of ends of semi-exceptional leaves, and Ghys freeness result in real-analytic regularity. Our first result concerns groups of real-analytic diffeomorphisms with infinitely many ends: if the action is non-expanding, then the group is virtually free. The second result is a Duminy type theorem for minimal codimension-one foliations: either non-expandable leaves have infinitely many ends, or the holonomy pseudogroup preserves a projective structure. © 2019 London Mathematical Society
Keywords: 20000000; 37C85 (primary); 37D25; 37F15; 57S05 (secondary)